2019
DOI: 10.1016/j.ajog.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and outcomes of assisted reproduction

Abstract: Background.-There is growing acceptance that nutrition may be related to fertility, and specifically to ART success in women; however, there is still no specific dietary guidance. Objective.-To evaluate the relationship between pre-treatment adherence to various dietary patterns and outcomes of assisted reproductive technologies (ART). Study Design.-We followed 357 women enrolled in the prospective Environment and Reproductive Health (EARTH) Study, who underwent 608 ART cycles (2007-2017). Using a validated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
133
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(139 citation statements)
references
References 32 publications
2
133
1
3
Order By: Relevance
“…Evidence studying the relationship between diet and fertility is rarely regarding foods or dietary patterns and mostly oriented to single nutrients [ 267 ]. Humans do not typically consume antioxidants or nutrients in pure form.…”
Section: Future Directions: Foods and Dietary Patterns In Male Infmentioning
confidence: 99%
“…Evidence studying the relationship between diet and fertility is rarely regarding foods or dietary patterns and mostly oriented to single nutrients [ 267 ]. Humans do not typically consume antioxidants or nutrients in pure form.…”
Section: Future Directions: Foods and Dietary Patterns In Male Infmentioning
confidence: 99%
“…Zahlreiche Studien stützen die These, dass eine Einhaltung der MD, ein hoher Score bei der Diät oder der Verzehr bestimmter Bestandteile der Diät (Fisch, Milchprodukte etc.) zu einer Verbesserung der Raten für klinische Schwangerschaften und Lebendgeburten nach In-vitro-Fertilisation (IVF) führen [2] [3]. Jedoch ist die Generalisierbarkeit einzelner Studien auf alle Frauen mit Fertilitätsproblemen nicht möglich.…”
Section: Die Mediterrane Diät Als Perikonzeptionelle Ernährungsformunclassified
“…Jedoch ist die Generalisierbarkeit einzelner Studien auf alle Frauen mit Fertilitätsproblemen nicht möglich. Eine strengere Einhaltung der MD war mit einem besseren IVF-Ausgang assoziiert, aber es wurde keine dosisabhängige Beziehung festgestellt [2].…”
Section: Die Mediterrane Diät Als Perikonzeptionelle Ernährungsformunclassified
See 1 more Smart Citation
“…Two studies from Europe, by Vujkovic et al (2010) and Karayiannis et al (2018) , reported that a greater adherence to a ‘Mediterranean diet’ pattern (rich in vegetable oils, fish, legumes, whole grains and low in meat) preconception, enhanced the odds of achieving a successful pregnancy through ART. Further to this, a study group from the USA classified 357 women undergoing ART into quartiles based on adherence to four different dietary patterns—MedDiet, Fertility diet, Alternate Healthy Eating Index 2010 and profertility diet ( Gaskins et al , 2019 ). Contrary to findings from the European studies, they showed no additional improvement in live birth rate above the second quartile of adherence to the MedDiet.…”
Section: Introductionmentioning
confidence: 99%